Foreign direct investment, oil prices and global financial crisis: Evidence from Singapore - Wong, Koi Nyen *; Goh, Soo Khoon; Hooi, Hooi Lean (European Research Center of Managerial Studies in Business Administration, 2015)
Foreign direct investment (FDI) is often cited as an important feature of the Singapore’s economy. In addition to its contribution to the city states’ capital formation, it also fosters international trade, technology transfer and yields other spillover effects. Despite Singapore economy is highly internationally linked, it cannot insulate itself against external shocks e.g. the Asian financial crisis, global financial crisis, and oil price shocks, to name a few. This study attempts to ascertain whether the effects of external shocks on the sources of FDI in Singapore are transitory or permanent using the Lagrange multiplier (LM) unit root tests proposed by Lee and Strazicich (2003 and 2004). The empirical evidence reveals that the external shocks had only transitory effects on FDI regardless of the source of the FDI either by region, major investor country or other investor country. The findings provide policy measures on how the government should best respond to shocks that affect FDI in the city-state in the short run.